External intervention and social capital promotion bridging the institutionalist gap - Ventura, Brian C.; Fernandez, Pepito R., Jr (Danyag :the UPV journal of humanities and social sciences, 2009)
"There are two competing perspectives in understanding the potential effects of external intervention for social capital promotion. The first perspective considers social capital as a product of long and complex process of historical, economic and social changes, making intervention unhelpful if not counterproductive. The second perspective posits social capital as a product of institutional arrangements and community characteristics, and can therefore be enhanced. This article follows the second perspective in understanding social capital promotion but argues that within this perspective there are existing gaps. These gaps can be classified into three; the problem of potential number of cooperation participants; follow through organizations and prevention of factor distortion; and leadership development. This article proposes that with th use of community organizing these structural-community characteristics gaps can be bridged."